Hijaiyah Letter Learning Media Application for Early Age Muslim Children Based on Android - Pandu Surya Nugraha; Fika Putri Mardiani (Journal of Multimedia Trend and Technology, 2023)
Introducing hijaiyah letters to children needs to be increased in terms of intensity and media. To increase the intensity and efficiency of delivery, supporting media is needed that is packaged in an attractive, relaxed, and interactive manner. Early childhood education is essential because at that stage the teaching system will influence children's behavior and thinking patterns. One of the necessary early childhood education is learning to spell. Spelling is pronouncing or saying letters one by one. This word spelling education can be supported with game-based learning media. Based on the results of the author's interviews with Early Childhood Education teachers at Raudlatul Jannah, information was obtained that the process of learning to recite the Koran, especially introducing hijaiyah letters, had not yet achieved optimal results, therefore the author aimed to design and build an Android-based hijaiyah letter learning media application to improve students' understanding. hijaiyah letters and as a fun learning support media. The results of this research are that a hijaiyah letter learning media application has been successfully developed and declared suitable as an auxiliary media for learning for early childhood at the Raudlatul Jannah school.